Topical Problems Of Patriotic Education At Younger Schoolchildren In The Modern Conditions - Mailybaeva, G.S.; Tulegenova, G.A.; Janzakova, Sh. I.; Nurgaliyeva, S.A.; Assylova, R.O. (Opción, 2019)
The presented work considers the problem of patriotic education at schoolchildren as one of the priority directions of Kazakhstan’s social development in modern conditions via comparative qualitative research methods. As a result, the paradoxically of the modern situation consists that today’s domestic education can be characterized as uncertain, unstable, internally contradictory. In conclusion, the ability to coordinate personal with the public, as one of the most important criteria of patriotic good breeding, is still insufficiently developed at younger school age